A New Impedance-Based Main and Backup Protection Scheme for Active Distribution Lines in AC Microgrids - Nobakhti, Seyyed Mohammad; Ketabi, Abbas; Shafie-khah, Miadreza (MDPI, 2021)
Microgrids active characteristics such as grid-connected or islanded operation mode, the distributed generators with an intermittent nature, and bidirectional power flow in active distribution lines lead to malfunction of traditional protection schemes. In this article, an impedance-based fault detection scheme is proposed as the main protection of microgrids by applying the proposed equivalent circuits for doubly-fed lines. In this scheme, relay location data and positive sequence voltage absolute value of the other end of the line are used. It can detect even high impedance faults in grid-connected and islanded modes. It is robust against load and generation uncertainties and network reconfigurations. Low sampling rate and minimum data exchange are among the advantages of the proposed scheme. Moreover, a backup protection scheme based on the conductance variations is suggested. No requirement for the communication link is a distinguished advantage of the proposed backup protection scheme. The proposed schemes have been simulated using PSCAD and MATLAB software and the results confirmed their validity.
Keywords: backup protection; distributed generation; distribution network; fault detection; impedance-based protection; main protection; microgrid; fi=Sähkötekniikka|en=Electrical Engineering|